Editorial: symptom improvement does not equal satisfaction with treatment for constipation—authors' reply. Issue 9 (14th April 2020) - Basilisco, Guido; Barbara, Giovanni; Bellini, Massimo; Cataudella, Giovanni; D'Alba, Lucia; Guarino, Michele; Iovino, Paola; Neri, Maria Cristina; Sarnelli, Giovanni; Savarino, Edoardo; Tolone, Salvatore; Torresan, Francesco; et al.
Abstract : LINKED CONTENT This article is linked to Basilisco et al and Ballou and Lembo papers. To view these articles, visit https://doi.org/10.1111/apt.15657 and https://doi.org/10.1111/apt.15683 .